Numerical Study of the Effect of Furrows on Biosonar Beamforming in Aselliscus Stoliczkanus Bat - HE, Weikai; FENG, Jianxiong; GAO, Li; ZHANG, Zhiwei; LU, Hongwang (Archives of Acoustics, 2017)
The Aselliscus Stoliczkanus bat, studied here, has intricately shaped structures surrounding the nostrils. These structures are hypothesised to have influence on animals’ acoustic radiation patterns. Using micro-tomography scanning technique, a 3D digital model of the noseleaf is reconstructed and biosonar beam pattern is analysed using a finite element method based on the 3D noseleaf model. The present research focuses on the conspicuous furrows in noseleaf, and our analysis allows to conclude the followings: a) structural details in noseleaf of Aselliscus Stoliczkanus bat can produce acoustic effects even if it is not adjacent to the nostrils, b) the furrows possess frequency-selective characteristics, c) the furrows have the function to manipulate the direction and width of the outgoing ultrasound wave.